An Exploratory Study to Assess Knowledge Regarding Birth Preparedness among Primigravida in a Selected Hospital of a Metropolitan City - Loladiya, Nilofar; Pagunti, Saipooja; Sadhu, Bhavna; Sadhu, Bhavna; Johnson, Jency (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: An exploratory study was conducted to assess knowledge regarding birth preparedness among primigravida in a selected hospital of a metropolitan city. Materials and Methodology: An exploratory research design and qualitative research approach was adopted and non-probability convenient sampling technique was used to select 50 primigravida mothers (n = 50). A structured interview technique was performed for collection of data Section A - Demographic variables, Section B Knowledge questionnaire. Results: The findings showed that majority of the subjects were in the age group of 22–25 years and 26–29 years with a frequency of 36% and 44%, respectively. Minimum of the subjects were in the age group of 18–21 years with a frequency of 20%. Majority of the subjects were Hindu, with a frequency of 64%. About 2% of the subjects were Buddhist. Majority of the subjects were house wives, with a frequency of 74%. Minimum of the subjects were corporate employees, with a frequency of 20%. All the subjects, 100% had yearly income within the range of 10–11 lakhs per annum. Majority of the subjects 38% for graduates whereas 26% had completed secondary education. Maximum of the subject 60%, were of the opinion that birth preparedness encompasses the holistic process of planning for normal birth and anticipating the actions needed in emergency care. Birth preparedness is strategy to promote the timely use of skilled maternal and neonatal care according to 16% of the subjects. About 8% of the subjects opined birth preparedness is the registration of pregnancy and institutional delivery whereas birth preparedness for 8% of subjects is majority of the subjects 98%, opined that exercise and meditation can help the pregnant woman to cope with stress. Conclusion: The primary objective to assess the knowledge of primigravida mothers regarding birth preparedness was achieved by the analysis of section I and II. Out of all the subjects, majority had good knowledge on whereas.